AFFECTATION CARTOGRAPHY FOR NATURAL HAZARDS IN POÁS CANTON, COSTA RICA - Barrantes-Castillo, Gustavo (2016)
Despite the existence of historical reports, compilations, databases and reports in Costa Rica that summarize zones affected by natural hazards since colonial times, there is not well-located historical information available in the country. Through a compilation and georeferencing of all the available informationregarding impacts of natural hazards that affected the Poas canton, it was possible to create spatial indicators of the recorded events (ash falling, volcanic gases, earthquakes, floods, and landslides). The different natural hazards were standardized in five classes (very low, low, moderate, high and very high),which allowed creating a maximum impact indicator overlapping the disaster records of Poas canton. The results of this study show a tendency to generate increased impact by natural hazards from south to north, which is consistent with the distribution of rainfall, slopes, and proximity to seismic and volcanicsources. These outcomes also showed a different pattern in flash floods and landslides related to the presence of river valleys with steep slopes in elongated and small basins on recent volcanic deposits.    Keywords: